Pengaruh Pemasaran Media Sosial Terhadap Niat Berlangganan : (Studi pada Pengakses Akun Instagram @spotifyid) - Moch. Praba Chasa Dhana; Aripin Ahmad (Universitas 45 Surabaya, 2023)
Spotify is a global company operating in the media sector. Spotify products are services streaming music subscription that offers thousands of songs and podcast. This research aims to review how social media marketing can influence the interest in subscribing from the Spotify Indonesia audience on Instagram. The results of this research will be used to evaluate and make recommendations for social media marketing strategies to increase subscription intentions in Spotify Indonesia on Instagram. Researchers conducted a quantitative survey of 120 respondents. The sample consists of respondents who have and can access an Instagram account, know Starbucks Indonesia and are over 18 years old. Data analysis uses Multiple Linear Regression Analysis and hypothesis testing uses the t-test processed with SPSS software ver. 26. From the results of testing the five hypotheses, it can be concluded that variable entertainment, interaction, word of mouth, and trend have a significant effect on subscription intentions. Meanwhile, variable customization does not have a significant effect on subscription intentions.